Unlocking gut-liver-brain axis communication metabolites: energy metabolism, immunity and barriers - Xiaoge Sun; Manish Shukla; Wei Wang; Shengli Li (npj Biofilms and Microbiomes)
Abstract The interaction between the gut-microbiota-derived metabolites and brain has long been recognized in both health and disease. The liver, as the primary metabolic organ for nutrients in animals or humans, plays an indispensable role in signal transduction. Therefore, in recent years, Researcher have proposed the Gut-Liver-Brain Axis (GLBA) as a supplement to the Gut-Brain Axis. The GLBA plays a crucial role in numerous physiological and pathological mechanisms through a complex interplay of signaling pathways. However, gaps remain in our knowledge regarding the developmental and functional influences of the GLBA communication pathway. The gut microbial metabolites serve as communication agents between these three distant organs, functioning prominently within the GLBA. In this review, we provide a comprehensive overview of the current understanding of the GLBA, focusing on signaling molecules role in animal and human health and disease. In this review paper elucidate its mechanisms of communication, explore its implications for immune, and energy metabolism in animal and human, and highlight future research directions. Understanding the intricate communication pathways of the GLBA holds promise for creating innovative treatment approaches for a wide range of immune and metabolic conditions.